1994
DOI: 10.1038/bjc.1994.267
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive lymphomas with renal involvement: a study of 48 patients treated with the LNH-84 and LNH-87 regimens

Abstract: S_nmry In order to describe renal involvement in aggressive non-Hodgkin's lymphomas (NHLs) and its prognostic significance, we reviewed the outcome of 48 patients with renal involvement treated with the LNH-84 or LNH-87 regimen. Histology was diffuse large cell in 29 (60%) patients; immmunoblastic, diffuse mixed cell and lymphoblastic in four each; follicular large cell, diffuse small cleaved cell and diffuse small non-cleaved cell in one each; and unclassified in four. Ann Arbor stage was IV in 44 patients, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…This would be useful information to gauge the value of FNA for excluding renal lymphoma and could guide future studies. Follow-up was only available for 26 patients; mortality was high for this heterogeneous group of patients but appears consistent with the literature [1]. …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This would be useful information to gauge the value of FNA for excluding renal lymphoma and could guide future studies. Follow-up was only available for 26 patients; mortality was high for this heterogeneous group of patients but appears consistent with the literature [1]. …”
Section: Discussionsupporting
confidence: 81%
“…However, renal lymphoma presents a unique challenge to this practice, as it typically responds well to chemotherapy [1] which can avert surgery. While extranodal spread of non-Hodgkin lymphoma frequently affects the kidneys, primary renal lymphoma is very rare.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] This may underestimate the true involvement, however, as older autopsy series reveal that the incidence may be as high as 50% in patients who ultimately succumb to their disease. 9,[20][21][22][23] Renal parenchymal involvement does not necessarily result in impaired organ function, suggesting that a number of patients may have microscopic, subclinical kidney involvement at diagnosis.…”
Section: Clinical Factor Chop (N=12) R-chop (N=8)mentioning
confidence: 99%
“…Such studies showed rapid improvement in renal function and tumor size, but treatment failure was common. 9,11,12 The addition of rituximab appears to improve both progression-free and overall survival rates. However, it does not appear to reduce rates of CNS relapse, although this conclusion is limited by our small sample size.…”
Section: Clinical Factor Chop (N=12) R-chop (N=8)mentioning
confidence: 99%
See 1 more Smart Citation